(untitled) (Journal of Human Sciences, 2026)
This study addresses the Kurdish issue as one of the prominent national questions in the Middle East, due to its complex historical, political, and legal dimensions, The research aims to analyze the origins and development of the Kurdish issue within the context of the transformations the region experienced after World War I, particularly the division of predominantly Kurdish areas among several states and the accompanying policies of denial and marginalization of Kurdish national identity, The study employs a historical and analytical methodology to examine the trajectory of the Kurdish issue, tracing its stages of development, analyzing the policies of the states concerned toward the Kurds, and exploring the demands of Kurdish movements, which range from cultural and political rights to autonomy, federalism, and the right to self-determination, The research also addresses the regional and international dimensions of the Kurdish issue and the impact of geopolitical changes on its course, The study concludes that the persistence of the Kurdish issue is primarily due to the absence of comprehensive political solutions based on the recognition of ethnic pluralism and the protection of Kurds’ legitimate rights within constitutional and legal frameworks, It emphasizes that addressing the Kurdish issue requires a peaceful approach grounded in dialogue, respect for human rights, and the insulation of the issue from regional conflicts, thereby contributing to stability and coexistence in multiethnic societies.